PENGARUH PEMANGKASAN CABANG UTAMA DAN PEMBERIAN PUPUK PELENGKAP CAIR ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Ruth Patricia Pasaribu; Husna Yetti; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to look the effect of main branch pruning, giving the liquid organic fertilizer complementary and interaction and get the best treatment on growth and yield of Tomato (Lycopersicum esculentum Mill.). This research was conducted experimentally by using Completely Randomized Design with two factors and three replications. The first factor was the main branch pruning consists of two levels (P0= no pruning, P1= pruning a main branch). The second factor was the concentration of liquid organic fertilizer complementary, which consists  of  five  levels  (K0= 0 ml/l water,  K1= 1 ml/l water,  K2= 2 ml/l water, K3= 3 ml/l water, K4= 4 ml/l water). Data were analyzed using analysis of variance and mean separations with Duncan’s New Multiple Range Test at the 5% level. The results showed that the main branch pruning has significantly to number of flowers. Giving the liquid organic fertilizer complementary has significantly to the age of first harvest. The interaction of the main branch pruning and giving the liquid organic fertilizer complementary has not significantly to all parameters. The main branch pruning treatment and giving the liquid organic fertilizer complementary 2 ml/l water showed plant height, fruit number per plant, weight per fruit, fruit diameter, total fruit weight per plant tend highest. Keywords:    tomato plant, the main branch pruning, liquid organic fertilizer complementary, growth and yield.